The Responses of Maritime Department Students toward Online Learning at the third semester during the COVID-19 Pandemic at Politeknik Negeri Bengkalis - Aprizawati Aprizawati (INOVISH JOURNAL, 2022)
The aim of this study is to investigate the process of online learning in this pandemic as well as effective and optimal for students’ online learning. The coronavirus disease (COVID-19) pandemic forced many universities to apply online learning. The design of this research is descriptive qualitative research. The data has collected by using observation, questionnaires, interviews, and documentation. Hopefully, this study will find which one is the most interesting online learning way by the lecturers to teach especially at the third semester students of Maritime Department, Politeknik Negeri Bengkalis. There are WhatsApp Group, Zoom, Google Meet and Google Classroom that the lecturers always use at this department. The study will suggest for students in online learning and the development of other media to implement effective online lectures that other researchers expose the solution to get more experience.Keywords: Students, Responses, Learning, Pandemic